#TITLE_ALTERNATIVE# - RAHAYU RIZKY (NIM 15105049); Pembimbing: Ir. Dina A Sarsito, MT., dan Dr. Ir. Irwan Meilano, , SILVYA
Sulawesi has the most faulting area in Eastern part of Indonesia which very susceptible to tectonic activity. Those thing caused by Sulawesi is part of East Indonesia that meets the three (3) tectonic plate, which are Hindia-Australia plate, Pacific plate, and Eurasian plate. The result of this tectonic activity are the spreading of fault formed throughout Sulawesi, one of those active fault is Palu-Koro Fault in Center of Sulawesi Province. Palu-Koro Fault is one of the case of the geodynamics that observed through precision GPS (Global Positioning System) observation. Based on observation GPS on year 2005, 2006, and 2007 from GPS stations that located spread out on faulting zone, the horizontal movement of the fault is 10-30 mm/years. Result of movement vector showed that Palu-Koro fault is categorized on left lateral strike slip fault type. The purpose of Deformation analysis in this paper is to determine the movement pattern of fault deformation, and then calculate slip rate and locking depth of that fault itself. Based on calculation, Palu-Koro fault has slip rate ranging from 32- 36 mm/years which locked at depth 5-6 km. This deformation analysis is useful to predict the strength of earthquake happening around the fault zone in long period of time.